Strategies and practices for cultivating students' critical thinking in the primary school basic education stage - Yao, Yilin (Edelweiss Applied Science and Technology, 2025)
During the basic education stage of primary school, cultivating students' thinking ability is one of the cores of educational work. With the advent of the information age, simply imparting knowledge is no longer sufficient to cope with the complex and changing social needs. Cultivating students' critical thinking (SCT) has become the key to improving the quality of education. Critical thinking not only helps students think independently and analyze problems in their studies, but also promotes the development of their innovation and lifelong learning abilities. This paper first explores the importance and current status of cultivating critical thinking in primary school students, and then analyzes the shortcomings of existing research. Next, this paper proposes targeted training strategies and verifies the effectiveness of these strategies through experimental design. The experiment includes two main strategies: one is to introduce project-based learning through classroom reform to encourage students to actively explore, question, and reflect; the other is to establish a diversified evaluation system to focus on students' thinking processes and innovation abilities. Finally, the paper discusses the experimental results in detail, demonstrating significant improvements in SCT after the implementation of the strategy. The experimental results show that after adopting the above strategies, students’ scores on observation and analysis abilities in critical thinking tests have improved, with their analysis abilities far exceeding those of the control group by about 14 points.